From Ambiguity to Deceptiveness: the Case of Hybrid since- Subordinates in English - Bénédicte GUILLAUME (E-REA)
When since is used as a subordinator,it can introduce either a temporal adverbial clause or a causal one. My purpose in this paper is to study cases in which such a polysemy at the level of the subordinator results in the production of subordinates whose meaning proves to be ambiguous between the categories of time and cause. In addition to the taking into account of the context, whether exophoric or endophoric, I put forward a series of syntactic criteria which should help disambiguate between the two possible interpretations. These are based on the study of the characteristics of nearly five-hundred examples of since- clauses taken from the one-hundred-million-word British National Corpus of contemporary English. Still, a handful of examples resist such a disambiguation, thus matching my definition of a ‘hybrid subordinate’ as a clause which challenges the traditional categorisation of subordinates in English, as it happens to possess at least one property which is not in keeping with the type to which it ought to belong according to most of its other characteristics. Such cases call for the grammar of any given language to allow for a ‘remainder’, to borrow Jean-Jacques Lecercle’s term.